2000
DOI: 10.3758/bf03211820
|View full text |Cite
|
Sign up to set email alerts
|

The traveling salesman problem: A hierarchical model

Abstract: Our review of prior literature on spatial information processing in perception, attention, and memory indicates that these cognitive functions involve similar mechanisms based on a hierarchical architecture. The present study extends the application of hierarchical models to the area of problem solving. First, we report results of an experiment in which human subjects were tested on a Euclidean traveling salesman problem (TSP) with 6 to 30 cities. The subject's solutions were either optimal or near-optimal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(160 citation statements)
references
References 19 publications
6
154
0
Order By: Relevance
“…A number of theoretical accounts have suggested that how people solve TSPs is, in part, based on perceptual processes (Graham et al, 2000;MacGregor et al, 2000). It seems plausible that, for very simple problems, perceptual processing predominates but, as problem diffi culty increases, more analytical processes come into play.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of theoretical accounts have suggested that how people solve TSPs is, in part, based on perceptual processes (Graham et al, 2000;MacGregor et al, 2000). It seems plausible that, for very simple problems, perceptual processing predominates but, as problem diffi culty increases, more analytical processes come into play.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, human solutions are often better than those of the simpler heuristic procedures (Graham, Joshi, & Pizlo, 2000;MacGregor & Ormerod, 1996). In addition, while the computational times per node for successful heuristic procedures typically increase as a function of the number of nodes, it seems that human solution times per node remain constant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. TSP modelers and researchers may do well not to focus exclusively on replicating the high quality of human performance and consider successful replications as support for their models (see also Graham et al, 2000;Pizlo et al, 2006). Instead it may be better to evaluate TSP models on the basis of risky predictions; after all, if a model passes a test based on a risky prediction, then this counts as genuine support for the model (see also Meehl, 1997;Roberts & Pashler, 2000).…”
Section: Methodological Afterthoughtmentioning
confidence: 99%
“…This observation has motivated researchers to set out to identify the human strategy for solving TSPs and implement it in a computational model. In this paper, we take a closer look at one such model, the Convex-hull (CH) algorithm model proposed by MacGregor, Ormerod, and Chronicle (2000), and its purported fi t to human performance on the TSP (for altogether different modeling attempts for TSP see Graham, Joshi, & Pizlo, 2000;and Pizlo et al, 2006). The CH model of MacGregor et al (2000) is a formal algorithmic elaboration on the convex-hull hypothesis put forth by MacGregor and Ormerod (1996;see van Rooij, Stege, & Schactman, 2003, for an overall assessment of the empirical support for this hypothesis) that proposes that people construct solutions to the TSP by fi rst perceiving (and mentally sketching) the boundary of the point set (called the convex hull) and then inserting one by one the interior points in the tour.…”
Section: Introductionmentioning
confidence: 99%